The Bonny Dawn: An Annotated Translation of Style and Clarity - Putri, Septian Dwi (Journal of Language and Literature, 2019)
This article is based on an annotated translation research. This research which belongs to the area of translation with commentary. The object of the research is an English novel The Bonny Dawn, written by Catherine Cookson. The research problem is what are the annotated translation of style and clarity in the novel The Bonny Dawn. Therefore, the aim of the research is to find out the translation style and clarity of the research object. This research used qualitative method and purposive random sampling technique as data collection procedure. The Chesterman principals of translation are employed as tool of analysis. The results of this research show that out of 11 data. The Finding of the research are Calque (2 items), Cohesion Change (2 items), Expansion (2 items), Explicitness Change (1 item), Interpersonal Change (2 items), Literal Translation (2 items).